Unearthly / 1. - Hand, Cynthia, 1978- (Unearthly, 2011)
Sixteen-year-old Clara Gardner's purpose as an angel-blood begins to manifest itself, forcing her family to pull up stakes and move to Jackson, Wyoming, where she learns that danger and heartbreak come with her powers.